Recent advances in the genetic basis of taste detection in Drosophila - Chen, Yu-Chieh David; Dahanukar, Anupama (Cellular and molecular life sciences : CMLS, 2020)
The insect gustatory system senses taste information from environmental food substrates and processes it to control feeding behaviors. Drosophila melanogaster has been a powerful genetic model for investigating how various chemical cues are detected at the molecular and cellular levels. In addition to an understanding of how tastants belonging to five historically described taste modalities (sweet, bitter, acid, salt, and amino acid) are sensed, recent findings have identified taste neurons and receptors that recognize tastants of non-canonical modalities, including fatty acids, carbonated water, polyamines, H 2 O 2 , bacterial lipopolysaccharide (LPS), ammonia, and calcium. Analyses of response profiles of taste neurons expressing different suites of chemosensory receptors have allowed exploration of taste coding mechanisms in primary sensory neurons. In this review, we present the current knowledge of the molecular and cellular basis of taste detection of various categories of tastants. We also summarize evidence for organotopic and multimodal functions of the taste system. Functional characterization of peripheral taste neurons in different organs has greatly increased our understanding of how insect behavior is regulated by the gustatory system, which may inform development of novel insect pest control strategies.